Codes of Journalism Ethics in Russia and the United States: Traditions and the Current Practice of Application - Bykov, Aleksei Yuryevich; Georgieva, Elena Savova; Danilova, Yuliya Sokratovna; Baychik, Anna Vitalyevna (International Review of Management and Marketing, 2015)
The purpose of the article is to identify the main categories stated in the codes of journalism ethics in Russia and the United States, as well as the principles of their practical application. As a part of the comparative analysis of the codes of the journalism organizations of the two countries, we identify factors affecting the adoption and contents of the documents and the approaches to the regulation of different areas of professional activity which were reflected in these documents. The author applies the method of historical study (comparative historical method), the logical method of a comparative analysis of documents, i.e. the codes of professional ethics (the attention is paid both to substantive and quantitative aspects), elements of the situation analysis. The key issues addressed in the article include the legal, political and professional traditions that predetermined the emergence of the codes of journalism ethics in Russia and the United States of America; the algorithm of regulating a journalist’s relationships with other participants of his professional career (a journalist and the audience of a publication, a journalist and the sources of information, etc.); practical approaches to resolving ethical issues arising in the process of journalist’s work. The findings of the study show that the historical conditions of the development of the two states, as well as their political traditions, influenced the development of journalism and formation of the professional journalism culture. These factors predetermined the specific features of the codes of journalism ethics in Russia and the United States, in particular, the time of the adoption of the first codes, the current number of such codes, their substantive features, specifics of their implementation. Keywords: code of ethics, journalism standards, freedom of speech, political traditions JEL Classifications: Z13; Z18